Enhancement of CO2RR product formation on Cu-ZnO-based electrodes by varying ink formulation and post-treatment methods. (16th February 2023) - Jaster, Theresa; Albers, Simon; Leonhard, Armin; Kräenbring, Mena-Alexander; Lohmann, Heiko; Zeidler-Fandrich, Barbara; Özcan, Fatih; Segets, Doris; Apfel, Ulf-Peter
Abstract: Numerous catalysts have been reported with enhanced performance, e.g. longer lifetime and improved selectivity, for the electrochemical CO2 reduction reaction (CO2 RR). Respectively little is, however, known about the influence of the electrode structuring and pre-treatment on this reaction for catalytic layers. Thus, we herein report on the modification of the catalyst environment of a Cu-ZnO-carbon black catalyst by variation of the ink composition and subsequent electrode treatment before performing CO2 RR. We furthermore provide insight into the impact of different solvents, ionomer, and additives like pore forming agents used for the ink preparation as well as post-treatment steps in terms of pressing and sintering of the generated electrodes on the CO2 RR performance. Although using the same catalyst for all electrodes, remarkable differences in hydrophobicity, surface morphology, and electrochemical performance with respect to stability and product distribution were observed. Our study reveals the critical role of the catalytic layer assembly aside from using proper catalysts. We furthermore show that the parasitic hydrogen formation and flooding behavior can be lowered and C2+ product formation can be enhanced when operating in optimized gas diffusion electrodes.